Return on Assets dan Capital Intensity terhadap Agresivitas Pajak Perusahaan Manufaktur Sub-Sektor Industri dan Kimia - Aznur, Dinda; Nazariah, Nazariah; Ramzijah, Ramzijah; yanti, evi maulida (Akuisisi : Jurnal Akuntansi, 2024)
This research is quantitative research that focuses on looking at the influence of Return On Assets (ROA) and Capital Intensity on Tax Aggressiveness. The difference in recognition of asset depreciation between commercial accounting financial reports and fiscal financial reports is a way for companies to reduce tax burdens. When a company has recognized depreciation expenses but in taxation these expenses are not included in the company's expenses, then the amount of expenses that are not included in the company's expenses will be added as a reversal of the reduction in income by these expenses. so that there will be an increase in taxable income which will increase the company's total expenses. The data collection method used is documentation from annual financial reports from 2017-2022. The data analysis techniques used are descriptive statistics, classical assumption tests, and panel data regression analysis which is estimated using the Common Effect Model. Based on hypothesis testing using simultaneous tests, it was concluded that Return On Assets (ROA) and Capital Intensity (CI) had no significant effect on Tax Aggressiveness where the p-value (0.9397) > alpha (0.05). Partial testing concluded that Return On Assets (ROA) had a significant effect on Tax Aggressiveness with a p-value (0.0071) while Capital Intensity (CI) had no effect on Tax Aggressiveness with a p-value (0.8289) > alpha (0.05).